Azobenzene‐bridged diradical janus nucleobases with photo‐converted magnetic properties between antiferromagnetic and ferromagnetic couplings. Issue 20 (5th March 2018) - Zhao, Peiwen; Bu, Yuxiang
Abstract : We computationally design a series of azobenzene (AB)‐bridged double radicalized nucleobases, a novel kind of diradical Janus‐type nucleobases, and explore their spin coupling characteristics. Calculations prove that such diradical Janus‐bases not only normally match with their complementary bases, but also exhibit well‐defined diradical character with photo‐convertible intramolecular magnetic couplings (antiferromagnetic vs. ferromagnetic). Combination of four radical nucleobases (rG, rA, rC, rT) and photoswitch AB can yield 10 diradical Janus‐bases with different magnetic characteristics in which AB functions a bridge to mediate the spin coupling between two radical bases. The trans ‐form supports mild antiferromagnetic couplings with the spin coupling constants ( J ) ranging from −153.6 cm −1 to −50.91 cm −1 while the cis ‐form has weak magnetic couplings with ferromagnetic (0.22–8.50 cm −1 ) for most of them or antiferromagnetic (−0.77, −1.73, −3.30 cm −1 ) properties for only three. Further structural examination and frontier molecular orbital analyses indicate that the extended π conjugation for better spin polarization provides an effective through‐π‐bond pathway to mediate the spin coupling in the trans conformation while nonplanarity of the cis conformation weakens the through‐bond coupling and causes a competitive through‐space pathway and as an overall result inhibits the spin coupling between two spin moieties. Meanwhile, we also find that the J values of the cis conformation vary with their angle between the radical base and its linked phenylene. Furthermore, the magnetic properties of the diradical Janus‐bases can be significantly increased by interacting with metal ions. They also maintain a good UV absorption characteristics and there is a clear redshift compared with AB. This work provides a promising strategy for the rational design of photo‐convertible Janus‐base magnets as the magnetism‐tunable DNA building blocks. © 2018 Wiley Periodicals, Inc. Abstract : A series of azobenzene‐bridged double radicalized nucleobases, a novel kind of diradical Janus‐type nucleobases, were computationally designed. Exploration of their spin coupling characteristics proves that such diradical Janus‐bases not only normally match with their complementary bases, but also exhibit well‐defined diradical character with photo‐convertible intramolecular magnetic couplings (antiferromagnetic vs. ferromagnetic).